Search for neutral resonances decaying into a Z boson and a pair of b jets or ? leptons - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; Friedl, M.; et al. (My University, 2016)
A search is performed for a new resonance decaying into a lighter resonance and a Z boson. Two channels are studied, targeting the decay of the lighter resonance into either a pair of oppositely charged ? leptons or a bb pair. The Z boson is identified via its decays to electrons or muons. The search exploits data collected by the CMS experiment at a centre-of-mass energy of 8 TeV, corresponding to an integrated luminosity of 19.8 fb-1. No significant deviations are observed from the standard model expectation and limits are set on production cross sections and parameters of two-Higgs-doublet models. © 2016 The Author.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Woods, N. (2016). Search for neutral resonances decaying into a Z boson and a pair of b jets or ? leptons. Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 759, 369-394. doi:10.1016/j.physletb.2016.05.087
Keywords: 2Hdm; B-Tagging; Bsm; Cms; Higgs; Lepton